Role of Propriospinal Neurons in Control of Respiratory Muscles and Recovery of Breathing Following Injury - Jensen, Victoria N.; Alilain, Warren J.; Crone, Steven A. (Frontiers in Systems Neuroscience, 2020)
Respiratory motor failure is the leading cause of death in spinal cord injury (SCI). Cervical injuries disrupt connections between brainstem neurons that are the primary source of excitatory drive to respiratory motor neurons in the spinal cord and their targets. In addition to direct connections from bulbospinal neurons, respiratory motor neurons also receive excitatory and inhibitory inputs from propriospinal neurons, yet their role in the control of breathing is often overlooked. In this review, we will present evidence that propriospinal neurons play important roles in patterning muscle activity for breathing. These roles likely include shaping the pattern of respiratory motor output, processing and transmitting sensory afferent information, coordinating ventilation with motor activity, and regulating accessory and respiratory muscle activity. In addition, we discuss recent studies that have highlighted the importance of propriospinal neurons for recovery of respiratory muscle function following SCI. We propose that molecular genetic approaches to target specific developmental neuron classes in the spinal cord would help investigators resolve the many roles of propriospinal neurons in the control of breathing. A better understanding of how spinal circuits pattern breathing could lead to new treatments to improve breathing following injury or disease.